Fostering Character Through Roller Skating: A Descriptive Analysis of Fair Play, Problem Solving, and Discipline Among Bandung Athletes - Maharani, Viola Nadia; Carsiwan, Carsiwan; Abduljabar, Bambang; Gumilar, Agus (JUMORA: Jurnal Moderasi Olahraga, 2025)
Character development of adolescents through physical activities is an effective medium in supporting athlete development, especially in forming values such as fair play, problem solving, and discipline. This study aims to analyze the level of implementation of fair play, problem solving, and discipline values in 39 roller skate athletes in Bandung City, and to identify factors such as gender and education level that influence the internalization of these values. This study used a quantitative descriptive design with a Likert scale-based questionnaire as the main instrument. The collected data were analyzed using descriptive statistical methods with the help of IBM SPSS. The results showed that the fair play value had the highest average score of 28.59 (SD = 2.98), reflecting good internalization among athletes. Meanwhile, the problem solving and discipline values each had an average score of 24.51 (SD = 3.20) and 26.87 (SD = 2.94), indicating the need for further strengthening. The analysis also revealed that gender and education level factors had a significant influence on the implementation of these values, where female athletes and high school athletes scored higher. Overall, this study shows that the values of fair play, problem solving, and discipline in roller skate athletes in Bandung City have been well internalized, with fair play as the most dominant value. Female athletes and high school athletes dominate the level of internalization of these values. Roller skating can be an effective means to shape the character of athletes. However, strategic steps are needed to optimize athlete development holistically